(In)constitucionalidade e (in)convencionalidade na ausência de fundamentação da decisão que recebe a acusação no processo penal brasileiro - Costa, João Santos da (2022)
The present work focuses on the purpose of restructuring, in terms of significance, the concept of judicial reasoning in criminal proceedings as from the decision that receives the accusatory claim in the admissibility phase, prior to the investigation and judgment. The investigation is supported on two epistemic axes, conventionality control and criminal procedural guarantees. The first suggests the implementation of conventional norms directly and immediately within the scope of criminal procedural jurisdiction as a condition of processability, that is, of legitimation of the process itself. The second aims to demonstrate that the judicial decision, as an act of power circumspect to cognitive, ethical and normative elements, will find in the concept of adequate reasoning a space for controlling the conventional guarantees of due process. It is a work based on inter and transdisciplinary research that values inductive and systemic methods insofar as it lends itself to organizing knowledge in favor of the construction of a new mentality. Thus, the inference resulting from the context of theories of conventionality and jus-philosophical studies around the concept of power suggest a new theoretical contribution to the concept of adequate foundations in criminal proceedings. The thesis reached is suggested in pragmatic terms, so that the decision that receives the complaint, either public or private, that does not exclude the violation of conventional guarantees of due process, specifically those contained in the American Convention on Human Rights, will not be recognized as duly substantiated. KEY-WORDS: Conventionality; Power control; Legitimation; Motivation